Bahan Ajar Inklusif Untuk Anak-Anak Dengan Spektrum Autism Di Kelas Reguler Sekolah Dasar: Sebuah Kajian Pustaka Penerapan Program Aba Dan Teacch - Fajarwati, Desi; Baharudin (Program Studi Manajemen Pendidikan Islam, 2024)
The autism rate according to the World Health Organization (WHO) as of 2023 is 1 in 100 children, which is likely to continue to increase. Children with Autism Spectrum Disorder (ASD) as part of the disabled community have the right to receive education in accordance with the mandate of the United Nations (UN) in various declarations. The presence of inclusive education is a solution to equal education for people with disabilities, including children with ASD. ASD children with all their varied behavioral symptoms require more study of the learning curriculum so that educational goals can be achieved. So the of this article is to combine existing research regarding learning programs for children with ASD in inclusive education, namely the Applied Behavior Analysis (ABA) program and Treatment and Education of Autistic and related Communication Handicapped children (TEACCH). The method used is literature study in journals related to ABA and TEACCH as well as inclusive education for children with ASD, journal screening using the InOrdinatio method. It is hoped that the ABA program combined with TEACCH will become a curriculum benchmark for learning for children with ASD, in addition to combining teacher skill factors through training and support from parents and families of children with ASD.